Forced Eruption: Alternative Treatment Approach to Restore Teeth with Subgingival Structure - Hamid Kermanshah; Elmira Najafrad; Sara Valizadeh (Hindawi Limited, 2022)
The management of teeth with deep caries, fracture, or perforation in the cervical third of the root is an integral part of dental practice. Orthodontic extrusion preserves the natural root system and may convert the tooth indicated for extraction into useful tooth with good prognosis and a low risk of failure. Orthodontic tooth eruption can be an alternative to treatment such as surgical crown lengthening, especially in esthetic areas, and provides more favorable conditions for prosthodontic coronal restorations by guaranteeing proper sealing and esthetics and preserving periodontal tissue health. The aim of this case report was to explain a multidisciplinary approach that successfully preserve and treat the teeth with subgingival carious lesion. This innovative method is cost-effective and can be easily done with the equipment available in any office.